Lipoprotein-associated phospholipase A2 and carotid intima-media thickness in primary Sjögren syndrome - Selcan Gültuna,; Sevinç Can Sandıkçı,; Hatice Kaplanoğlu,; Fevzi Nuri Aydın,; Funda Seher Özalp Ateş, (Archives of Rheumatology, 2022)
Objectives: This study aims to evaluate serum lipoprotein-associated phospholipase A2 (Lp-PLA2) level and carotid intima-media thickness in primary Sjögren syndrome (pSS) as an indicator of atherosclerosis. Patients and methods: Between July 2019 and July 2020, a total of 33 female pSS patients (mean age: 44.5±11.2 years; range, 23 to 60 years) and 37 female age- and sex-matched healthy individuals (mean age: 40.9±7.2 years; range, 25 to 54 years) were included. Carotid intima-media thickness and serum Lp-PLA2 levels were measured in the patient and control groups. Results: The patients had a higher median serum Lp-PLA2 of 560 (range, 108 to 1,222) ng/mL vs. 328 (range, 0 to 1,280) ng/mL in the controls (p=0.024) and a similar mean intima-media thickness of carotid artery (0.64±0.14 mm vs. 0.62±0.15 mm, respectively; p=0.595). Serum Lp-PLA2 was positively correlated with platelet count (r=0.411, p=0.018) and negatively correlated with erythrocyte sedimentation rate (r=-0.409, p=0.018). The mean value of carotid intima-media thickness was positively correlated with disease duration (r=0.316, p=0.074) and was negatively correlated with the level of leucocyte (r=-0.458, p=0.007). Conclusion: Our study suggests that the patients of pSS have a potential risk of atherosclerotic cardiovascular disease, independent of traditional cardiovascular risk factors and disease severity.